War, Migration, Memory: Perspectives on Russia's War Against Ukraine (Forum Transregionale Studien - Dossiers, 2024)
War and mass displacement in Ukraine triggered intensive reevaluations of the past and collective identities. The contributors to this volume examine how memory is mobilised and how cultural, collective, and individual memories are being reshaped to deal with the ruptures and threats posed by the war. They offer a multi-scalar perspective on the transformational effects of war and displacement on Ukrainian society in various contexts – local, regional, national, and global – and deal with shifts of memory and symbolic representations, experiences of dislocation, shifts in the linguistic and religious landscapes, gender roles, and repercussions of war on minority groups.